(3EOGQI GdCYeGd GdUZjQI (B:s (3CHYGO ddQjGOI (B/s - (3HQfhWj, SYGO fGjas ((3YeGf(B: s (3OGQ hGFd(B, s, 2005)
(3GdYed GdUZjQ(B-(3CgejI GdCYeGd GdUZjQI(B-(3NUhUjGJ GdYed GdUZjQ(B-(3GdCTcGd GdbGfhfjI dedcjI GdCYeGd GdUZjQI(B-(3hXGFa GdeOjQ(B-(3hXGFa GdJShjb(B-(3hXjaI GdYedjGJ hGdEfJGL(B-(3EOGQI GdehGQO GdeGdjI(B-(3hXjaI GdYedjGJ hGdEfJGL(B-(3hXjaI GdJShjb(B-(3EOGQI GdehGQO GdeGdjI hGdTDhf GdeMGSHjI(B-(3hXGFa GdeOjQs
Keywords: (3EOGQI GdCYeGds; (3GdTQcGJ GdUZjQIs